Organ preservation for patients with anterior mucosal squamous cell carcinoma of the nasal cavity: Rhinectomy‐free survival in those refusing surgery. Issue 8 (1st April 2019) - Mimica, Ximena; Yu, Yao; McGill, Marlena; Barker, Christopher A.; McBride, Sean; Ganly, Ian; Cracchiolo, Jennifer R.; Dunn, Lara A.; Katabi, Nora; Sine, Kevin; Mah, Dennis; Lee, Anna; et al.
Abstract: Background: Standard treatment of squamous cell carcinoma (SCC) of the anterior nasal mucosa is surgical resection with or without postoperative radiation. Methods: Retrospective review of patients diagnosed with SCC of the nasal cavity between January 2000 and July 2018 who refused total rhinectomy and who were treated with radiation with or without chemotherapy with curative intent. Results: Eleven patients were identified, 73% had stage III or stage IV disease. Four patients were treated with intensity‐modulated radiotherapy and seven with intensity‐modulated proton radiotherapy. Concurrent chemoradiotherapy was used in nine patients (82%). With a median follow‐up of 15 months (3‐124 months), two patients experienced recurrence and one developed distant metastasis and died from disease. The 2‐year rhinectomy‐free survival rate was 88%. Two‐year overall survival and recurrence‐free survival were 100% and 75%, respectively. Conclusion: A radiation‐based approach for SCC of the nasal cavity mucosa is a valid option for selected patients who refuse up‐front surgery.